Molecular screening of Bartonella in free-ranging capybaras (Hydrochoerus hydrochaeris) from Paraná State, Southern Brazil - Dos Santos, Nelson Jessé Rodrigues (2022)
Bartonella is an emerging group of facultative intracellular bacteria causing circulatory and systemic disorders. Hosts for Bartonella are mostly mammals, specifically rodents, having a growing number of Bartonella species related to their infection. Capybaras (Hydrochoerus hydrochaeris) are abundant native rodents of Brazil, commonly found in urban parks. In the present study, we aimed to perform molecular screening of capybaras for Bartonella spp. Blood samples were collected from 17 free-ranging animals captured in Paraná State, Southern Brazil. None of the collected samples tested positive for the Bartonella-nuoG gene by quantitative polymerase chain reaction (qPCR), although all of them successfully amplified the mammal endogenous glyceraldehyde-3-phosphate dehydrogenase (gapdh) gene. Additionally, all animals were infested exclusively by Amblyomma dubitatum ticks at the time of sampling. This study was part of an active surveillance program, which is critical for monitoring animal health status, particularly in capybaras.